Role of transoral robotic surgery in surgical treatment of early‐stage supraglottic larynx carcinoma. Issue 4 (24th February 2023) - Papazian, Michael R.; Chow, Michael S.; Jacobson, Adam S.; Tran, Theresa; Persky, Mark S.; Persky, Michael J.
Abstract: Background: There are several options for primary surgical treatment of early‐stage supraglottic squamous cell carcinoma (SCC), including transoral robotic surgery (TORS). The purpose of this study was to compare outcomes of TORS to open partial laryngectomy and transoral laser microsurgery (TLM). Methods: Patients with clinical classification T1‐2 supraglottic SCC diagnosed 2010–2019, treated with TORS, open partial laryngectomy, or TLM in the National Cancer Database were selected. Results: One thousand six hundred three patients were included: 17% TORS, 26.5% TLM, 56.5% open. TORS patients had the lowest rates of adjuvant treatment (28.4% vs. TLM: 45.0%, open: 38.5%, p < 0.001), and lower positive margin rates than TLM (16.9% vs. 30.5%, p < 0.001). Thirty‐day and ninety‐day post‐operative mortality did not differ between the approaches. Five‐year survival was higher following TORS compared to open surgery (77.8% vs. 66.1%, p = 0.01); this difference persisted following matched‐pair analysis. Conclusions: TORS may be a safe and effective surgical approach for early‐stage supraglottic SCC in appropriate patients.